Waterfront City dengan Pendekatan Arsitektur Berkelanjutan Di Kota Parepare - Kurnia, Elvira Dewi; A’raaf Tauhid, Fahmyddin; Rahayu, Irma (TIMPALAJA : Architecture Student Journals, 2023)
Pare-Pare City or commonly referred to as "Pare-Pare Harbor City" is the second-largest city in South Sulawesi Province which is located on the west coast of Sulawesi Island and has 20 percent of its area is a coastal area. Therefore, the coastal area of Pare-Pare City is an area that can be developed so that it can become a productive and efficient area. To minimize damage and create a projected area into the future, in the effort to develop the waterfront city we apply a sustainable architectural approach to the circulation system and use of materials to create a coastal city area with the efficient circulation that is interconnected in achieving from the city center to the waterfront city and between functions in the area and also the use of sustainable materials.